2018
DOI: 10.1002/ese3.234
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of collection, thermal, and conductivity efficiency of a solar distiller pond as a free concentration unit in wastewater treatment process

Abstract: The performance of one solar pond as a passive step in distilled and potable water production from desalination effluent is surveyed in this research. This solar pond is proposed in a zero discharge desalination process to prevent the salinity shocking which is made by a brackish water stream that exists from desalination units. The solar pond performance is evaluated by measuring three types of efficiency, experimentally, and mathematically. The efficiencies which are defined and calculated from experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Results showed that the added nano plate and vacuum pump can efficiently augment the evaporation rate, and the average daily production is increased by 16% compared to the conventional solar still. Farahbod (2016Farahbod ( , 2018 evaluated the efficiency of a solar distiller pond as a free concentration unit in wastewater treatment process. A research about the effects of nanofluid on the productivity of a stepped solar still has been conducted (Rashidi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the added nano plate and vacuum pump can efficiently augment the evaporation rate, and the average daily production is increased by 16% compared to the conventional solar still. Farahbod (2016Farahbod ( , 2018 evaluated the efficiency of a solar distiller pond as a free concentration unit in wastewater treatment process. A research about the effects of nanofluid on the productivity of a stepped solar still has been conducted (Rashidi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent studies in solar ponds have focused on composition solutions, [1][2][3] geometrical structures, [4][5][6] storage methods, [7][8][9] and hybrid configurations. [10][11][12] However, the number of studies on heat extraction enhancements is very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the replacement of renewable energy fossil fuels such as solar energy has been welcomed to reduce energy costs and reduce pollutant emissions 6 . Fortunately, Iran has very good insolation intensity in most areas, because it is located between the circuits 25°–40° north latitude 7 . This requires the implementation of solar plans and allows the use of solar energy in cities and 60,000 dispersed villages in the country.…”
Section: Introductionmentioning
confidence: 99%